A 'good job' in difficult conditions: Detectives' reflections, decisions and discriminations in the context of 'joint enterprise'. (August 2020) - Young, Tara; Hulley, Susie; Pritchard, Gary
'Joint enterprise' is described as a 'dragnet' that draws disproportionate numbers of black and minority ethnic young men into the criminal justice system in England and Wales. While stereotyping by the police and prosecution has been blamed for this distributive injustice, empirical research on joint enterprise is limited. This article presents the findings from a study of homicide and 'gang' detectives in London in which they rebut accusations of racial stereotyping when investigating multi-handed crimes. Instead, they claim that the disproportionality reflects the involvement of larger numbers of primarily black men in violent crime. Using Margaret Archer's social realist theory, detectives frame their actions as being driven by their 'ultimate concerns' to do a good job of protecting the public and obtaining justice for victims within the difficult social and cultural context in which they operate. However, in this article, we expose the racialized notions of risk in detectives' narratives and argue that such 'colour-blind racism' is likely to contribute to young black and mixed-race men being overrepresented in cases that draw on the principles of joint enterprise dragging those on the periphery of group violence into the criminal justice net.